2018
DOI: 10.12928/telkomnika.v16i1.6848
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Parameter of Nonlinear Bias Correction Method Using NSGA-II in Daily Precipitation Data

Abstract: Nonlinear (NL) method is the most effective bias correction method for correcting statistical bias when observation precipitation data can not be approximated using gamma distribution. Since NL method only adjusts mean and variance, it does not perform well in handling bias on quantile values. This paperpresents a scheme of NL method with additional condition aiming to mitigate bias on quantile values. Non-dominated Sorting Genetic Algorithm II (NSGA-II) was applied to estimate parameter of NL method. Furtherm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Recently, machine learning algorithms have also been introduced for satellite precipitation bias correction. Pratama et al (2018) combined genetic algorithm with a power transformation method for satellite precipitation bias correction. Le et al (2020) used a neural network to correct satellite precipitation bias in the Mekong River basin.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, machine learning algorithms have also been introduced for satellite precipitation bias correction. Pratama et al (2018) combined genetic algorithm with a power transformation method for satellite precipitation bias correction. Le et al (2020) used a neural network to correct satellite precipitation bias in the Mekong River basin.…”
Section: Introductionmentioning
confidence: 99%
“…This method has been used to solve many actual UCTP cases. There are several GA models such as informed GA [10], parallel GA [2], NSGA II [11,9], Adaptive Real Coded GA [13], Hybrid Fuzzy and GA [6], Quantum Evolutionary Computing [1], and distributed model GA [14] that have been proposed. This research used the distributed model GA, or what is known usually as Island Model GA [14], out of all these models.…”
Section: Introductionmentioning
confidence: 99%
“…However, [5] and [3] revealed that CHIRPS still showed systematic bias. [6] performed preliminary study to find out the performance of CHIRPS over Java Island, and concluded that CHIRPS still has systematic bias on statistical value.…”
Section: Introductionmentioning
confidence: 99%